A PENSION SYSTEM REFORM IN THE REPUBLIC OF MACEDONIA - Mustafai, Habil (International Scientific Journal Vision, 2017)
Pension system reforms process has been initiated in 1993 due to deficits of the Pension and Disability Insurance Fund (PDIF), low fertility rates, demographic aging and high unemployment rates in the country. Fully funded pension insurance differs radically from previously existing currently funded pension insurance in terms of treatment and records of contributions paid in respect of the determination and payment of the pensions. In this insurance each member has an individual account, which recorded its assets and provides a contribution, which increases the funds. The fully funded pension system, which consists of mandatory and voluntary pension insurance, provides only one type of fund selection to the insurers, or one portfolio for investing of their assets. That way insurer receives the same relation to the risk or same opportunities for contributions regardless of their desire and appetite. The desire and appetite for risk usually differ depending on the age of the insurer. Also, the composition of one portfolio increases the risk of loss of assets of older insurers without possibility for their return through the capital markets.With the establishment of the multifunds, the members of the system will be able to accumulate and invest their contributions according to their own choice. In this paper, the current pension system in Republic of Macedonia.